Metro Passenger Path Choice Behavior during Single-line Operation Interruption in Risk Emergencies - GUO Jingfan; TIAN Yuanyuan; LI Juncheng; HE Jiantao; LUO Qixiang (Chengshi guidao jiaotong yanjiu)
［Objective］ To gain insights into the impact of emergencies and incidents on urban rail transit passenger travel behavior, and assist operational departments in responding more effectively to operational disruptions caused by such occasions, a questionnaire is specially designed. ［Method］ The questionnaire design covers both fundamental questions (revealed preference—RP survey) and scenario-based questions (stated preference—SP survey), addressing emergency scenarios such as train fires, station flooding, and foreign object intrusion into tunnels, as well as various travel distance scenarios including short and long distances on the same line and between two lines. The questionnaires are collected through offline distribution at various stations within the Guangzhou Metro network and online via the official public account, gathering a total of 3,000 valid responses. Based on these questionnaire data, multinominal Logit (logistic regression), abbreviated as MNL, models are established to quantitatively analyze the influence degrees of factors such as travel time, travel cost, and travel frequency on passenger travel choices. ［Result & Conclusion］ Passenger travel choices are influenced by multiple factors, including the type of emergency, travel distance, and travel period. Notably, in short-distance travel scenarios on the same line, shared bicycles account for an average of over 4.5% of the alternative travel choices. The established MNL models can evaluate the impact of different diversion measures on passenger choice probabilities, providing valuable decision support for operational departments. Future research will focus on further predicting OD (origin-destination) demand, redistributing passenger flow, and assessing the effectiveness of diversion measures to optimize response strategies.